2014
DOI: 10.1093/mnras/stu1804
|View full text |Cite
|
Sign up to set email alerts
|

The triggering of starbursts in low-mass galaxies

Abstract: Strong bursts of star formation in galaxies may be triggered either by internal or external mechanisms. We study the distribution and kinematics of the H I gas in the outer regions of 18 nearby starburst dwarf galaxies, that have accurate star-formation histories from HST observations of resolved stellar populations. We find that starburst dwarfs show a variety of H I morphologies, ranging from heavily disturbed H I distributions with major asymmetries, long filaments, and/or H I-stellar offsets, to lopsided H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 119 publications
(164 reference statements)
11
96
0
Order By: Relevance
“…For the galaxies with resolved observations, for comparison with CO, we have attempted to compute the H I mass, M HI , by integrating the mean H I surface density within only the optical radius. Because virtually all metal-poor dwarf galaxies show H I emission well outside their optical radius (e.g., Hunter et al 1994a;van Zee et al 1998;van Zee 2000;Ekta et al 2009;Lelli et al 2012Lelli et al , 2014, these values of M HI are typically a factor of 2-10 lower than the total H I mass, integrated over the entire H I extent. Table 1 reports both values of M HI when resolved H I maps are available.…”
Section: H I Measurementsmentioning
confidence: 99%
“…For the galaxies with resolved observations, for comparison with CO, we have attempted to compute the H I mass, M HI , by integrating the mean H I surface density within only the optical radius. Because virtually all metal-poor dwarf galaxies show H I emission well outside their optical radius (e.g., Hunter et al 1994a;van Zee et al 1998;van Zee 2000;Ekta et al 2009;Lelli et al 2012Lelli et al , 2014, these values of M HI are typically a factor of 2-10 lower than the total H I mass, integrated over the entire H I extent. Table 1 reports both values of M HI when resolved H I maps are available.…”
Section: H I Measurementsmentioning
confidence: 99%
“…In the case of dwarf galaxies it has been suggested that interactions are responsible for the class of blue compact dwarfs (BCDs; Paudel et al 2015): dwarf galaxies with a significant, centrally concentrated young stellar population (e.g., Gil de Paz et al 2003). In general many dwarf systems with increased star formation rates (SFR) have been found to be irregular or to show signs of disturbances (Taylor et al 1995;Ekta & Chengalur 2010;López-Sánchez 2010;Holwerda et al 2013;Lelli et al 2014b;Knapen & Cisternas 2015), but in a number of cases no visible companion has been found (Brosch et al 2004;Ekta & Chengalur 2010;López-Sánchez 2010;Lelli et al 2014b). Other possible origins of the increase in star formation and the irregular morphology are cosmological gas inflows (see for example Verbeke et al 2014) or re-accretion of material blown out by previous starbursts, and varying internal instabilities (e.g., Meurer et al 1998;van Zee et al 2001;Lelli et al 2014a;Elmegreen et al 2012;Bekki & Freeman 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These lower-mass galaxies are important, as are minor mergers (e.g., Kaviraj 2014), because they contribute significantly to the evolution of the overall galaxy population (e.g., Lelli, Verheijen & Fraternali 2014;Stierwalt et al 2015).…”
Section: Introductionmentioning
confidence: 99%